2015
DOI: 10.1146/annurev-micro-091014-104441
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas: New Tools for Genetic Manipulations from Bacterial Immunity Systems

Abstract: Prokaryotic CRISPR-Cas loci encode proteins that function as an adaptive immune system against infectious viruses and plasmids. Immunity is mediated by Cas nucleases and small RNA guides, which specify a cleavage site within the genome of the invader. In type II CRISPR-Cas systems, the RNA-guided Cas9 nuclease cleaves the DNA. Cas9 can be reprogrammed to create double-strand DNA breaks in the genomes of a variety of organisms, from bacteria to human cells. Repair of Cas9 lesions by homologous recombination or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
155
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 138 publications
(189 reference statements)
1
155
0
1
Order By: Relevance
“…A short and conserved protospacer adjacent motif (PAM) sequence near the target site is required for the cleavage process of Cas9 [9,10]. CRISPR-Cas9 has been extensively used for genome editing in various cell types and organisms [11,12]. A series of structural studies of Streptococcus pyogenes Cas9 (SpyCas9) and its orthologs have revealed the detailed intermolecular interactions, as well as the conformational changes among different substrate-bound states [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A short and conserved protospacer adjacent motif (PAM) sequence near the target site is required for the cleavage process of Cas9 [9,10]. CRISPR-Cas9 has been extensively used for genome editing in various cell types and organisms [11,12]. A series of structural studies of Streptococcus pyogenes Cas9 (SpyCas9) and its orthologs have revealed the detailed intermolecular interactions, as well as the conformational changes among different substrate-bound states [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/126722 doi: bioRxiv preprint first posted online Apr. 11, 2017; 2 The development of the CRISPR/Cas9 system [1][2][3][4], derived from an adaptive immune system in prokaryotes [5], has received much recent attention, in part due to its exceptional versatility as a gene editor in sexually-reproducing organisms, compared to similar exploitations of homologous recombination such as zinc-finger nucleases (ZFNs) and the TALENS system [4,6]. Part of the appeal is the potential for introducing a novel gene into a population, allowing control of highly pesticide-resistant crop pests and disease vectors such as mosquitoes [7][8][9][10].…”
mentioning
confidence: 99%
“…By using sgRNA guides, tumorigenic colon cancer genes and SNPs in coding as well as non-coding regions can be studied and potentially destroyed. In addition, colon carcinoma promoting proteins such as deregulated protein kinase C isozymes, MYC effector proteins, and various inflammatory promoters, are viable targets for the programmable nucleases [3, 28, 29]. By understanding the implications behind its uses as well as concerns, CRISPR/Cas9 stands at the forefront of biomedical advances and serves to change the landscape of genetic engineering in a broad spectrum of clinical malignancies.…”
Section: Resultsmentioning
confidence: 99%